The Correlation between Healthcare Workers' Support and Compliance of COVID-19 Health Protocol Implementation in The Community - Farid Enggal Dwiyanto; Yulis Setiya Dewi; Lailatun Nimah (The Journal of Palembang Nursing Studies, 2022)
Background: The compliance of COVID-19 health protocol implementation in the community is one of the steps to prevent the spread of COVID-19. Purpose: This study aimed to analyze the relationship between the support of healthcare workers and the compliance with implementing COVID-19 health protocol in society. Methods: This research used a quantitative design with a cross-sectional approach. This research was conducted on society in Mojo Village, Gubeng District, Surabaya. The number of samples was 400 respondents with the cluster sampling technique. The results were analyzed using descriptive analysis and logistic regression test with a significance value of p ? 0.05. Results: Statistical tests showed that there was a relationship between the support of health workers and the compliance with implementing the COVID-19 health protocol in society with a significant value of emotional support (p=0.040), informational support (p=0.003), instrumental support (0.000), and appraisal support (0.011). These results indicated that instrumental support had the most influence on the level of compliance in implementing the COVID-19 health protocol in the community. Conclusion: The compliance with implementing the COVID-19 health protocol in the community is related to the emotional support, information support, instrumental support, and appreciation support of healthcare workers.